Geotechnical engineering : principles and practices - Coduto, Donald P. (Upper Saddle River, NJ : Prentice Hall, 1999)
For undergraduate-level courses in Introductory Geotechnical Engineering. This introduction to geotechnical engineering explores both the principles of soil mechanics and their application to engineering practice -- and offers a more rigorous -- yet still accessible and easy-to-read -- approach, more technical depth, and more emphasis on understanding the physical basis for soil behavior.
Includes bibliographical references (p. 725-742) and indexes.
Keywords: Geotechnical engineering